(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the importance of proper child upbringing in shaping a child’s character, behavior, and future success. It discusses the role of parents, education, environment, values, and emotional intelligence in raising children. The paper also presents common challenges and modern approaches to parenting in the 21st century.